Placement for Condition Monitoring of Rotating Machine Elements Based on HSD: Penempatan untuk Pemantauan Kondisi Elemen Mesin Berputar Berdasarkan HSD - Diah Prahmana Karyatanti, Iradiratu; Ramadhan , Muhammad Hakim (Muhammadiyah University, Sidoarjo, 2025)
Careful placement and selection of sensors is the key to accurate motorbike monitoring. This research aims to develop an optimal sound sensor placement strategy for monitoring the condition of induction motor bearing elements. Sensor placement will affect monitoring accuracy. The nature of sound signals is that they easily overlap with surrounding sounds. Different placement of sound sensors will provide opportunities for non-motor sounds to overlap. The bearing condition monitoring system was developed in real time by processing sound signals using fast Fourier transform (FFT). The sensor placement strategy needs to be taken into account so that monitoring results obtain high accuracy. The honestly significant difference (HSD) approach is a test used to determine the best sensor placement. Tests were carried out with variations in the placement of sound sensor distances and different levels of bearing damage. The results of the research are the best sensor placement at a distance of 110 cm from the motor body with a detection accuracy of 94.14%.